PEMANFAATAN DAUN MIMBA SEBAGAI PESTISIDA ORGANIK DI KECAMATAN KADEMANGAN KOTA PROBOLINGGO - Rusdi Rusdi; Titik Purwati; Budijanto Budijanto; Riyanto Riyanto (JPM PAMBUDI, 2017)
Science Program for Wiayah (IbW) is intended to empower the community to form Kademangan Sub-district in Probolinggo City which is more advanced, more prosperous and more faithful. This objective will be achieved by empowering communities through the development of science and technology based areas with a planned approach, in which communities are involved in the planning, implementation, evaluation and utilization of results. In particular the IbW Program is: (1) To identify potential, realistic, realistic, real, and realistic human resources, condition, and resources in Kademangan sub-district, Probolinggo Municipality; (2) To formulate the potential of human resources and natural resources so that it can be used as a commodity of superior territory; (3) Conducting training activities in the framework of technology transfer produced by Higher Education to the community. The methods used in this Program are survey, and observation. Preparation of action programs conducted through workshop activities. The results of the IbW program are: (1) The socialization of IbW Program with the Local Government of Probolinggo Municipality and the Pohsangit Kidul and Pilang Village Farmer Groups; (2) Counseling on the Benefits and Use of Pesticide Neighbors; (3) Training and practice of Mimba Leaf Processing Becoming Plant Pesticide. The conclusion of the IbW program is that it is very potential to develop bio-pesticide biological agents from neem. To cultivate vegetable pesticides especially from neem by farmers still needed the process and time because farmers are still familiar with chemical pesticides.